Influence of Post-Annealing on Properties of α-Ga2O3 Epilayer Grown by Halide Vapor Phase Epitaxy. (24th January 2019) - Son, Hoki; Choi, Ye-Ji; Hwang, Jonghee; Jeon, Dae-Woo
Abstract : Effect of annealing to realize high-quality α-Ga2 O3 epilayers grown by halide vapor phase epitaxy has been studied. The structural and optical properties of α-Ga2 O3 changed with changing annealing duration. In particular, for an annealing duration of 3 min, the crystal quality improved from 51 and 2757 arcsec to 28 and 1539 arcsec for (0006) and (10–14) FWHM, respectively. X-ray photoelectron spectroscopy results confirmed that the oxygen gas during annealing reacted to compensate the oxygen vacancies in the α-Ga2 O3 epilayers. These results show that the optimized thermal annealing improved the crystal quality of α-Ga2 O3 epilayers.